Effects of g-C3N4 on bacterial community and tetracycline resistance genes in two typical sediments in tetracycline pollution remediation - Hu, Xuemei; Chen, Xiaoyong; Tang, Yao; Xu, Zhenggang; Zeng, Yelin; Wang, Yonghong; Zhao, Yunlin; Wu, Yaohui; Wang, Guangjun (Frontiers in Microbiology, 2022)
Photocatalysis, as a novel technique, has been widely used for antibiotic pollution remediation in wastewater. In the processes of degradation and removal of antibiotics, the impact of photocatalysts on microenvironment is very important but remains poorly understood. In the present study, the effect of typical photocatalyst g-C3N4 (Graphitic carbon nitride) on microbial community was investigated in two sediment types (riverbed sediment and pig-farm sediment) polluted by tetracycline (TC) in central southern China. The riverbed sediment and pig farm sediment samples were respectively exposed to g-C3N4 (25, 75, 125 mg·kg-1) and TC (60, 120, 180 mg·L-1) treatments alone or combination for 30 days, respectively. The bacterial community and antibiotic resistance genes (ARGs) of the treated sediments were analyzed by Illumina sequencing and metagenomic sequencing. Studies had shown that: TC, g-C3N4, and TC/g-C3N4 have significant effects on the changes of microbial communities and components in riverbed sediment, but they do not exist in pig farm sediment. The most alterations of microbial taxa were Acidobacteriota, Actinobacteriota, and Desulfobacterota in riverbed sediment, and Elusimicrobiota in the pig farm sediment under various treatments. Through network analysis, it was found that the distribution of microorganisms in the pig farm sediment is more complex and more stable. The addition of g-C3N4 reduced the absolute abundance of ARGs in the two examined sediments, but not significantly changed their relative abundance of ARGs. The g-C3N4 application was beneficial to the removal of TC residues and to the prevention of the generation and transmission of ARGs in sediments. Our results suggested that g-C3N4 was a suitable photocatalyst with excellent application prospect for the removal of TC residues and the control of ARGs in environment.